2010
DOI: 10.1111/j.1748-1716.2010.02214.x
|View full text |Cite
|
Sign up to set email alerts
|

Urine concentrating mechanism in the inner medulla of the mammalian kidney: role of three‐dimensional architecture

Abstract: The urine concentrating mechanism in the mammalian renal inner medulla (IM) is not understood, although it is generally considered to involve countercurrent flows in tubules and blood vessels. A possible role for the three-dimensional relationships of these tubules and vessels in the concentrating process is suggested by recent reconstructions from serial sections labelled with antibodies to tubular and vascular proteins and mathematical models based on these studies. The reconstructions revealed that the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 61 publications
(153 reference statements)
1
29
0
Order By: Relevance
“…Model results of the present study support our hypothesis, described in previous reviews (7,24,33), that the countercurrent system in the CD cluster mixes NaCl absorbed from ATLs with absorbate from the CDs (which consists mostly of water, urea, and NaCl) to produce isolated sites of high osmolality that will promote water withdrawal from CDs. By isolating CDs from DVR, which carry relatively dilute fluid, the INSs increase water reabsorption from the CDs and raise the osmolality of its tubular fluid.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Model results of the present study support our hypothesis, described in previous reviews (7,24,33), that the countercurrent system in the CD cluster mixes NaCl absorbed from ATLs with absorbate from the CDs (which consists mostly of water, urea, and NaCl) to produce isolated sites of high osmolality that will promote water withdrawal from CDs. By isolating CDs from DVR, which carry relatively dilute fluid, the INSs increase water reabsorption from the CDs and raise the osmolality of its tubular fluid.…”
Section: Discussionsupporting
confidence: 91%
“…In the context of a countercurrent system, we have previously suggested (7,24,33) that the absorbate from the CDs and ATL is carried via the AVR to higher levels within the CD cluster, where the local absorbate will likely have lower solute concentrations and lower osmolality and where the ascension in AVR fluid that is concentrated relative to local fluid would raise the osmolality of the CD tubular fluid and contribute to an optimization of concentrating efficiency. The model predicts that AVR fluid is hypotonic relative to tubular fluid in loops of Henle, CDs, and DVR.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The renal medulla contributes significantly to systemic blood pressure control through regulation of sodium excretion and fetal programming includes enhanced salt sensitivity of blood pressure (2,12). Normal salt excretion is a function that relies partly on the unique architecture and close tubulovascular relationship of the renal medulla (10). However, the contribution of renal medullary developmental changes to the programming effect of adult hypertension is not known.…”
mentioning
confidence: 99%
“…2,3 A similar arrangement of the surrounding vessels prevents osmotic gradient dissipiation. 4 Electron microscopy studies demonstrated the presence of two distinct cell types in the TAL, differing in the configuration of the apical membrane: rough-surface cells (R cells), characterized by abundant apical microvilli, and smooth-surface cells (S cells) with no microprojections, but with several subapical vesicles. 5 The former is abundant in the cortex, and the latter in the medulla.…”
mentioning
confidence: 99%